2021
DOI: 10.3390/v13102002
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion via Clodronate Pretreatment Reduces Transgene Expression from AAV Vectors In Vivo

Abstract: Adeno-associated virus is a popular gene delivery vehicle for gene therapy studies. A potential roadblock to widespread clinical adoption is the high vector doses required for efficient transduction in vivo, and the potential for subsequent immune responses that may limit prolonged transgene expression. We hypothesized that the depletion of macrophages via systemic delivery of liposome-encapsulated clodronate would improve transgene expression if given prior to systemic AAV vector administration, as has been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These molecules in turn promote immune cell induction and activation allowing the initiation and expansion of antitransgene and/or anti-capsid adaptive immune cells, primarily CD8+ T cells [86][87][88]. In line with our findings, the absence of AAV-mediated enhanced liver transduction following clodronate-induced macrophage inhibition was previously reported in 8-week-old C57BL6/J mice [50]. The different observations between lentiviral and AAV-mediated liver transduction In conclusion, our study shows that clodronate-induced macrophage inhibition enhances lentiviral-mediated liver transduction in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These molecules in turn promote immune cell induction and activation allowing the initiation and expansion of antitransgene and/or anti-capsid adaptive immune cells, primarily CD8+ T cells [86][87][88]. In line with our findings, the absence of AAV-mediated enhanced liver transduction following clodronate-induced macrophage inhibition was previously reported in 8-week-old C57BL6/J mice [50]. The different observations between lentiviral and AAV-mediated liver transduction In conclusion, our study shows that clodronate-induced macrophage inhibition enhances lentiviral-mediated liver transduction in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Pre-administration of clodronate liposomes followed by administration of adenoviral vectors depleted macrophages and allowed higher liver transduction in vivo [47][48][49]. In contrast, pre-administration of clodronate and AAV vector injection in vivo produced a considerable reduction in transgene expression in the liver [50].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that most people have already been exposed to wild-type AAVs [31], resulting in the development of an immune response against them. These patients, develop not only binding antibodies but also NAbs.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, different strategies can be used, for example using modi ed capsids [29]. AAV vectors also may be altered by pseudo-typing, using the capsid of a heterologous AAV [31]. This could be tricky when using a recombinant vector developed from non-human primates (NHPs), for example when using AAVrh10, a virus originated in rhesus macaques, about 59% of healthy human adults had antibodies against it, and 21% had NAb's [32].…”
Section: Discussionmentioning
confidence: 99%